2020
DOI: 10.3390/ijms21145165
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of CDK4/6 and PI3K/AKT/mTOR Signaling Impairs Energy Metabolism in MPM Cancer Cells

Abstract: Background: Malignant pleural mesothelioma (MPM) is an aggressive malignancy associated to asbestos exposure. One of the most frequent genetic alteration in MPM patients is CDKN2A/ARF loss, leading to aberrant activation of the Rb pathway. In MPM cells, we previously demonstrated the therapeutic efficacy of targeting this signaling with the CDK4/6 inhibitor palbociclib in combination with PI3K/mTOR inhibitors. Here, we investigated whether such combination may have an impact on cell energy metabolism. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
2
15
1
Order By: Relevance
“…Interestingly, CD36 overexpression not only increased the phosphorylation of Src but also activated its key downstream targets, namely PI3K and AKT. PI3K/AKT is an upstream regulator of mTOR, which is also crucial for the regulation of glycolysis by inducing glycolytic enzymes 40 , 41 . Thus, our results suggested that CD36 dramatically activates mTOR phosphorylation via Src/PI3K/AKT signal axis, resulting in enhanced glycolytic pathway, and ultimately promotes HCC growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD36 overexpression not only increased the phosphorylation of Src but also activated its key downstream targets, namely PI3K and AKT. PI3K/AKT is an upstream regulator of mTOR, which is also crucial for the regulation of glycolysis by inducing glycolytic enzymes 40 , 41 . Thus, our results suggested that CD36 dramatically activates mTOR phosphorylation via Src/PI3K/AKT signal axis, resulting in enhanced glycolytic pathway, and ultimately promotes HCC growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the available evidence supports a multifaceted and context-dependent role for CDK4/6 in metabolism [ 34 ]. A role for CDK4 in glycolysis has been described in mouse embryonic fibroblasts (MEFs), whereby CDK4 knockout impairs anaerobic glycolysis [ 17 ], whilst the CDK4/6 inhibitor palbociclib reduces glycolysis in triple-negative breast cancer [ 40 , 41 ] and mesothelioma [ 42 ]. Glucose metabolism also appears to underpin synergistic activities of palbociclib in combination with PI3K/mTOR inhibitors in triple-negative breast cancer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ER expression is required for a response to palbociclib plus endocrine therapy, other pathways may also affect the efficacy of palbociclib, such as the androgen receptor (AR) signalling pathway [ 42 ]. A single 18 F-FES PET scan failed to show crosstalk with other pathways; therefore, it would be of interest in future studies to add multiple molecular imaging probes to improve the predicted response to palbociclib-based treatment, such as 18 F-fluoro-5α-dihydrotestosterone ( 18 F-FDHT)-PET for imaging AR [ 43 ] and 18 F-FDG PET for imaging the glycolytic metabolism tumour burden [ 44 ]. Finally, we were unable to obtain serial tumour biopsies to assess ER status, especially liver metastases (ER status cannot be reliably measured in liver metastases due to high background 18 F-FES avidity), thus limiting information on the accuracy of the 18 F-FES PET imaging of ER status.…”
Section: Discussionmentioning
confidence: 99%